PENGARUH UPAH DAN INSENTIF TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. DELTA MERLIN SANDANG TEXTILE I SRAGEN - Muhammad Ali Rauuf; Rini Adiyani; Zandra Dwanita Widodo (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
The company needs a productive workforce but there are still employees who cannot achieve the target according to the plan/on time in a job. If the wages and incentives are not in accordance with the employee's work, it will cause problems with employee productivity. This study is intended to determine the effect of wages and incentives on work productivity of employees of PT. DMST 1 Sragen. Researchers use quantitative research. For the population in this study, namely all employees of the CD unit at PT. DMST I Sragen with 1000 employees. Meanwhile, when the population is more than 100, it can be taken as much as 10% or 20% - 25% more. Thus, 10% x 1000 = 100 samples are taken. The significance value of 0.000 < 0.05 shows that wages have a significant effect on the work productivity variable. A significance value of 0.512 > 0.05 indicates that incentives do not significantly affect the work productivity variable. The significance value of 0.000 is less than 0.05. It can be concluded that all independent variables (wages and incentives) in this study have a significant effect on work productivity. There is a significant influence between wage variables on employee work productivity at PT. Delta Merlin Clothing Textile 1 Sragen. There is no significant effect between the incentive variables on the work productivity of employees at PT. Delta Merlin Clothing Textile 1 Sragen. It is known that wages and incentives variables simultaneously have a significant effect on employee work productivity at PT. Delta Merlin Clothing Textile 1 Sragen.